Differentiated Teaching Module for Indonesian Language Based on Graphological Analysis of Letter I, R, G - Hamdani; Fitri Hartati; Novalina Setyaningrum (Studies in Learning and Teaching, 2023)
There are many ways that can be done to find out the individual characteristics of each student. The purpose of this study was to determine the internal potential of 10th Grade “Halimah” Students by using graphological analysis based on general characteristics, which is the slope of the writing direction, the slope of the writing lines, the spacing between words, and the spacing between lines, and based on the general characteristics, which are the letters "I", "R", and "G". This study uses a qualitative descriptive research method. This method is used to describe the general description of the research, which are the characteristics of handwriting with the internal potential of students and to interpret graphology in several aspects. Then, this type of descriptive research is also capable of solving practical problems in the development of science, especially for graphological research. The stages of this research are handwriting analysis, triangulation through interviews, grouping results. The results of the analysis show that the internal potential of students is variative, so that appropriate learning methods or approaches are needed in order to achieve individual student learning goals